Severe Bacterial and Plasmodium Falciparum Infections in Febrile Children with Sickle Cell Disease Receiving Organized Specialty Care in a Referral Center in Sub-Saharan Africa: lessons for Clinical Practice - Diallo, Dapa A; Baraïka, Mohamed Ag; Guindo, Aldiouma; Kéita, Ibrahim; Charrel, Remi; Coulibaly, Mody; Kanta, Mariam; Traoré, Assétou; Sarro, Yaya S; Touré, Boubacari A; Tessougué, Oumarou; Guindo, Pierre; et al. (Journal of Hematology Research, 2019)
The burden of severe bacterial and malaria infections in children with SCD has been reduced through the use of prophylactic antibiotics and chemoprevention with Sulfadoxine-pyrimethamine. However, such therapies have the potential to promote bacterial and parasitic resistance. To our knowledge, no study has been conducted to determine whether systematic use of prophylactic antimicrobials in children with SCD has an impact on resistance patterns in sub-Saharan Africa. The aim of our study was to determine the incidence and the outcome of severe bacterial and P. falciparum infections in this context. 231 children with SCD and new onset fever associated with either acute pneumonia, urinary tract infection, cholecystitis, meningitis, acute osteomyelitis, or P. falciparum infections were entered into the study. The children in the cohort were an average age of 93 months (± 44 months) and were all followed in a referral center in Western Africa. The 231 children represented 36.67% of the patients regularly followed in the center during the study period and included 183 SS, 26 SC, 12 S?°thal, 10 S?+thal. There were 144 boys and 87 girls in the cohort. The incidence of severe bacterial and Plasmodium falciparum infections were lower than those reported in the general pediatric or sickle cell population in the absence of regular follow-up (ie 5.2, 1.4, 1.0 and, 4.1 per 1000 person/month for urinary tract infections, acute pneumonia, bacteremia and P. falciparum malaria respectively). We observed bacterial strains to be mainly in the Enterobacteria family with high levels of antibiotic resistance. No cases of Streptococcus pneumoniae bacteremia were found. Sulfadoxine-pyrimethamine resistance was observed at high levels. In light of these findings, prophylactic antibiotherapy and antimalarial chemoprevention guidelines in sickle-cell children should be revisited in the context of organized SCD care in sub-Saharan Africa.